“Our City Will Be the First to Hold Both Summer and Winter Olympics”: A comparative analysis of how media coverage and public opinion were framed on social media in the lead up to the Beijing 2022 winter Olympic games - Yang, Zesheng; Ruan, Yang; Zhang, Jianing (Frontiers in Psychology, 2023)
Beijing is the first city to host both the Summer and Winter Olympics. This article examines how the news coverage of and public opinion about the Beijing 2022 Winter Olympics were articulated on social media. It does so through a computational content analysis of 9,439 individual posts and 450 news media posts that appeared in Beijing before the 2022 Olympics. The results of this analysis reveal that members of the public are more inclined to highlight certain aspects of Beijing 2022 based on their individual perspectives, with topics around entertainment stars being the most popular. News media, whose work generally aligns with the government’s interests, emphasise the work of preparing for Beijing 2022 preparation work. Through a sentiment analysis of these posts, we found strongly positive attitudes concerning Beijing 2022 among the Chinese public and the media. This indicates immense support for the event. This research has enhanced scholars’ understandings of the news media coverage of and public opinion regarding mega sporting events in the context of China.